PENERAPAN METODE DEMONSTRASI BERBASIS MEDIA CERITA LUCU BERGAMBAR DALAM PEMBELAJARAN MENULIS TEKS ANEKDOT PADA SISWA - Firmansyah, Fery; Firmansyah, Dida (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The research conducted in this article is to apply a method of media-based demonstration of funny pictorial stories in learning to write anecdotal text on students. The purpose of this research is to see the influence of media-based demonstration method of the funny story illustrated in the students. The reason for the implementation of the research because when students write anecdotal text they do not have the experience of a sarcastic story, so they do not find idea or idea. The quasi-experimental research method was chosen because it aims to test the effectiveness of demonstration methods and illustrated storytelling media on students' writing skills in anecdotal text writing lessons. The findings of an increase in writing an anecdotal text of students who initially pre-test value of 69.52 at the time of postest increased to 78.32. Mean value, Kolmogorov-Smirnov data normality test which states that the test score is normally distributed because the significance value (sig) is greater than 0.05 then H1 is accepted.